On the smoothness of the generalized solution of a parabolic system in domains with conic points on the boundary - Nguyen, Manh Hung; Pham, Trieu Duong (Ukrains’kyi Matematychnyi Zhurnal, 2004)
We consider the first initial boundary-value problems for parabolic systems in domains with conic pointson a boundary. We study the smoothness of their solutions with respect to spatial variables.